2009
DOI: 10.1080/02770900802448436
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Morbidity Attributed to Auto-exhaust Pollution in Traffic Policemen of Jaipur, India

Abstract: Respiratory morbidity with respect to lung function tests is observed more in groups working in heavy traffic than the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…However, there was slight decrease in the value for the study group. These findings contradict those of Wonsurakiat et al, Singh et al, Pal et al, and Sharat et al who found consistent difference in FVC and FEV1 between TPP exposed to vehicular emission and those not exposed [15][16][17][18].…”
Section: Discussioncontrasting
confidence: 64%
“…However, there was slight decrease in the value for the study group. These findings contradict those of Wonsurakiat et al, Singh et al, Pal et al, and Sharat et al who found consistent difference in FVC and FEV1 between TPP exposed to vehicular emission and those not exposed [15][16][17][18].…”
Section: Discussioncontrasting
confidence: 64%
“…In a study carried out in Hong Kong, PM 10 concentrations near busy streets were found to range from 25.56 to 337.4 μg/m 3 which were significantly higher than the nearby fixed station data [22]. A study conducted in Jaipur to evaluate pulmonary effects of traffic pollution on traffic police found higher respiratory morbidity in traffic policemen compared to an unexposed outdoor group [23]. These studies emphasize the need for personal monitoring of air pollutants which could reduce misclassification of exposure.…”
Section: Sensitivity Analysismentioning
confidence: 86%
“…23 In Jaipur, India, a significant decline in percentage of the predicted normal values of FEV 1 for TP (n ¼ 300) was observed compared with a healthy control group (n ¼ 164). 21 For TP (n ¼ 1603) in Hong Kong, prevalence of nonspecific respiratory disease in polluted, moderately polluted, and suburban areas was 13.0%, 10.9%, and 9.4%, respectively, indicating an association between prevalence of respiratory symptoms and urban traffic air pollution. 22 Although the sample size is limited, results on respiratory symptoms and spirometry do not show strong differences across occupations.…”
Section: Discussionmentioning
confidence: 98%